Characteristics of smoked catfish (mystus nemurus) smoked with different methods - M. Aldi Imamsyah; Suardi Loekman; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the quality of smoked catfish preparedwith hot smoking and liquid smoking method. Two gruops of catfish (± 500gr/fish) were prepared for smoked fish using acacia wood. One group was hotsmoked in a smoked kiln at 70 - 100 oC for 10 hours and another group was depthinto liquid smoke from the same wood for 60 minutes and ovendried at 60 oC for10-15 hours. The smoked fish were evaluated for consumer acceptence, moisture,phenol, acidity, and pH. The result showed that the smoked fish prepared by hotsmoking method was more acceptable than that liquid smoking method. Moisture,phenol, acidity, and pH for the smoked catfish smoked with hot smoking was9,33%, 7,26%, 3,43%, and 5,76, respectively and for smoked catfish smoked withliquid smoking was 8,17%, 4,63%, 2,13%, and 6,39 respectively.Keywords : Characteristics, smoked catfish, liquid smoking, hot smoking